Identification and analyses of genes associated with floral development in Sago palm (Metroxylon sagu) - Syahrul Bariyah, Anji (Universiti Malaysia Sarawak (UNIMAS), 2010)
Flowering process in plants is a complex system and involved various genes. Understandings of the role of genes involved in the flower development enable manipulation of aspects of the process in the future for crop improvement. In this study, efforts have been made to screen for CO and LFY. the genes that have been known to be the genes that are activated very early in flowering process. As for the LFYand CO, a few fragments have been successfully isolated and sequenced. DDRT -PCR method was also undertaken in order to identifY the genes that are expressed in various sago palm tissues namely the meristem, inflorescence and leaf tissue) Using .I this technique, differentially expressed genes were isolated, sequenced and identified from the selected tissues. The expression of the successfully identified genes such as sugar transporter, chitinase, photosystem I psaH protein, caffeic acid 3-0methyltransferase, l-aminocyclopropane-l-carboxylic acid oxidase, mitogen activated protein kinase, universal stress protein, dynein light chain and 40S subunit ribosomal protein S21 possibly be involved in the flower development or have other functions. Partial sequences of chitinase obtained from DDRT-PCR work was employed as a probe to further amplifY the 3'-end and 5'-end regions of sago palm chitinase. Repeated amplification and sequences analysis confirmed that 3'end region of chitinase cDNA have been successfully amplified. However, the amplification of the complete sequences of the chitinase cDNA in the sago palm is not accomplished. A near complete chitinase cDNA isolated is 1143 bp long and contained 312 bp predicted amino acid. Alignment of nucleotide and amino acid have grouped this chitinase to the Domain Family 19 and Class I chitinase.